Rethinking the Nature of Fascism Comparative Perspectives - Pinto, António Costa; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
Many of the foremost experts in the study of European fascism unite to provide a contemporary analysis of the theories and historiography of fascism. Essays discuss the most recent debates on the subject and how changes in the social sciences over the past forty years have impacted on the study of fascism from various perspectives.
Keywords: World history; Historiography; Civilization-History.; World politics; Imperialism; Europe-History.; World History, Global and Transnational History; Historiography and Method; Cultural History; Political History; Imperialism and Colonialism; European History